2012
DOI: 10.1200/jco.2010.33.7089
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Study of Surgery Alone or Surgery Plus Preoperative Cisplatin and Gemcitabine in Stages IB to IIIA Non–Small-Cell Lung Cancer

Abstract: Although the study was terminated early, preoperative gemcitabine plus cisplatin followed by radical surgery improved survival in patients with clinical stage IIB/IIIA NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
171
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(192 citation statements)
references
References 27 publications
13
171
2
6
Order By: Relevance
“…In patients undergoing complete surgical resection adjuvant chemotherapy has been shown to benefit patients with pathological stage II-III disease (24,25). However, the ability for patients having a traditional thoracotomy to receive adjuvant chemotherapy has been limited.…”
Section: Discussionmentioning
confidence: 99%
“…In patients undergoing complete surgical resection adjuvant chemotherapy has been shown to benefit patients with pathological stage II-III disease (24,25). However, the ability for patients having a traditional thoracotomy to receive adjuvant chemotherapy has been limited.…”
Section: Discussionmentioning
confidence: 99%
“…But median survival varied within these groups of patients who received carboplatin and paclitaxel, the median survival was 10.18 months, 7.5 months in gemcitabine+carboplatin and 7 months in Cisplatin+etoposide regimen ( Table 2). The results of our study were in comparison with those reported by Scagliotti (2012) in their "clinical trialChEST", with a significant improvement in both disease free survival (DFS) (HR=0.51) and overall survival rate (HR=0.42) in patients with clinical stage IIB-IIIA NSCLC using preoperative gemcitabine plus cisplatin. However there was better improvement in Carboplatin+Paclitaxel regimen in the overall survival rate among the three treatment groups.…”
Section: Discussionmentioning
confidence: 45%
“…Пациенты со ста-дией заболевания N2 в набор не включались [12]. Исследователи планировали включить 712 пациен-тов, но исследование было закрыто преждевремен-но, когда было набрано всего 270 пациентов, после www.…”
Section: неоадъювантная химиотерапияunclassified
“…Общая выживаемость также была выше в группе химиотерапии. Исследователи задо-кументировали абсолютное трехлетнее улучшение в БРВ на 5.1% в группе «химиотерапия плюс опера-ция» и улучшение на 7.8% в 3-летней ОВ [12].…”
Section: неоадъювантная химиотерапияunclassified